Characterization and Genomic Study of Phage vB_EcoS-B2 Infecting Multidrug-Resistant Escherichia coli - Xu, Yue; Yu, Xinyan; Gu, Yu; Huang, Xu; Liu, Genyan; Liu, Xiaoqiu (Frontiers in Microbiology, 2018)
The potential of bacteriophage as an alternative antibacterial agent has been reconsidered for control of pathogenic bacteria due to the widespread occurrence of multi-drug resistance bacteria. More and more lytic phages have been isolated recently. In the present study, we isolated a lytic phage named vB_EcoS-B2 from waste water. VB_EcoS-B2 has an icosahedral symmetry head and a long tail without a contractile sheath, indicating that it belongs to the family Siphoviridae. The complete genome of vB_EcoS-B2 is composed of a circular double stranded DNA of 44283 bp in length, with 54.77 % GC content. vB_EcoS-B2 is homologous to fourteen relative phages (such as Escherichia phage SSL-2009a, Escherichia phage JL1 and Shigella phage EP23), but most of these phages exhibit different gene arrangement. Our results serve to extend our understanding towards phage evolution of family Siphoviridae of coliphages. Sixty-five putative open reading frames were predicted in the complete genome of vB_EcoS-B2. Twenty-one of proteins encoded by vB_EcoS-B2 were determined in phage particles by Mass Spectrometry. Bacteriophage genome and proteome analysis confirmed the lytic nature of vB_EcoS-B2, namely, the absence of toxin-coding genes, islands of pathogenicity, or genes through lysogeny or transduction. Furthermore, vB_EcoS-B2 significantly reduced the growth of E. coli MG1655 and also inhibited the growth of several multi-drug resistant clinical stains of E. coli. Phage vB_EcoS-B2 can kill some of the MRD E. coli entirely, strongly indicating us that it could be one of the components of phage cocktails to treat MRD E. coli. This phage could be used to interrupt or reduce the spread of MRD E. coli..